TINJAUAN TERHADAP TRADISI SEDEKAH BUMI DALAM PERSPEKTIF HUKUM ISLAM - Putri, Shekar Aulia (Jurnal Dinamika Sosial Budaya, 2023)
Indonesia is a country rich in unique and or arguably eccentric customs or traditions. One of the traditions that are still attached or still preserved by the community is the tradition of the earth or nyadran. In Kunti Village, Andong District, Boyolali Regency, the village alms tradition is held by the community once a year and usually this tradition is held after harvest expressing gratitude for the rice harvest from the community to Allah SWT who bestows sustenance by bestowing the rice harvest, as well as the purpose of this tradition is to clean the village from all logs or disasters and the community can also see the closeness to Allah SWT with blessings. This tradition, apart from being a form of cultural preservation by the community, also has an aspect to unite between citizens so that harmony is created in society, such as principle 3, namely "PERSATUAN INDONESIA". The earth alms ceremony is held to strengthen the solidarity of the people with one another.
Keywords: village alms; islam; culture